Perdagangan Anak Perempuan dan Strategi Penanganannya - Sriharini, Sriharini (Musawa Jurnal Studi Gender dan Islam, 2006)
This article examines on human trafficking, especially younggirls. Children as the next generation need to be secured for their save, welfare and also protected their rights. Sometimes in reality, it reflects opposite conditions. There is an apprehensive phenomena in society which is young girl trafficking. It can be considered as gender base violence that experienced by girls or practices that discriminate women. This violence can arise various problems of psychologies, physical, psychology, economic, and even sexual. Therefore, overcoming this women violence in the form of girl trafficking need to be prioritized. In effort to handle it, it needs to be preceded by socialization about girl trafficking to most of components society, so people pay attention toward the issues, and it is urgent to be struggled. Then, it implements a comprehensive program. Starting from preventing, protecting, rehabilitation, and reintegrating which are conducted by involving teachers, society religious teachers/leaders and government officials also decision makers in according with their own task.